Pemanfataan Ekstrak Kulit Buah Kopi Robusta dalam Pengembangan Produk Minuman Cendol Instan Fungsional dengan Sifat Antioksidan Tinggi dan Kafein Rendah - Putra, Reski Praja; Fitri, Fitri; Patang, Patang (Agricultural Technology Education Study Program, 2024)
This research aims to examine the effect of adding coffee fruit skin extract on the quality and functional properties of the instant cendol produced. This research consisted of two stages, namely coffee husk extraction using 70% ethanol and instant cendol formulation with 5 treatments adding a concentration of coffee husk extract, namely 0%, 3%, 4%, 5% and 6%. The observation parameters consist of rehydration time, chemical and microbiological quality, functional properties, and hedonic quality. This research used a Completely Randomized Design which was analyzed using the IBM SPSS application. The results showed that the concentration of added coffee fruit skin extract had a positive influence on the microbiological quality and functional properties of the instant cendol produced, but had no effect on the rehydration time, water content and hedonic quality of the instant cendol. The microbiological quality and functional properties of instant cendol treated with the addition of coffee fruit rind extract were better compared to the control treatment. The best instant cendol is produced from the addition of 6% coffee fruit skin extract. This formulation has a rehydration time and water content that meets standards, a microbial content of 5.1 Log colonies/ml, a caffeine content of 0.15%, anthocyanin content of 1.032%, a polyphenol content of 12.44%, and an antioxidant content of 17.99%. The resulting instant cendol also received good reception from the panelists.